EVALUATION OF GOLD MINE TAILINGS IN CEMENT MORTAR: INVESTIGATION OF THE EFFECTS OF CHEMICAL ADMIXTURES - Yildirim Ozen, Meral; Dur, Fatma; Kunt, Kubra; Moroydor Derun, Emek (YILDIZ TECHNICAL UNIV, 2020)
This study presents an experimental investigation on the influences of gold mine tailings as a substitute for cement. Various ratios of air-entraining and superplasticizer admixtures were used in the determined composition of gold mine tailing-containing mortars. Several analytical variables, including setting time, water absorption, and strength tests, were studied to establish the relationship between these added materials and the properties of cement mortars. In addition, the compositions of 28-day-cured samples were identified by X-ray diffraction (XRD) analysis. The results showed that when the water /binder (w/b) ratio is kept constant at 0.5, the replacement of cement by 10% gold mine tailing showed mechanical properties similar to those of the reference sample. The mortars prepared with 0.5% superplasticizer admixture reached the highest compressive and flexural strength values of 64.16 MPa and 8.99 MPa, respectively. When flowability and water absorption properties are improved by the air-entraining admixture addition, the compressive and flexural strength decrease.
Keywords: Cement mortar; chemical admixture; gold mine tailing; industrial waste; DURABILITY; CONCRETE; STRENGTH; SILICA; PASTE; Engineering